ANALISIS KESELAMATAN, KESEHATAN, LINGKUNGAN KERJA, DAN DISIPLIN KERJA BERPENGARUH TERHADAP PRODUKTIVITAS KERJA DENGAN METODE STRUCTURAL EQUATION MODELING - Suryanto Suryanto (Matrik : Jurnal Manajemen dan Teknik Industri Produksi, 2018)
Increasing productivity is a major concern across industries, as the company’s effectiveness and efficiency of resources into products that can be marketed and determine the business benefits. As a result, the various indicators and factors for consideration have been directed to increase productivity.This study aims to (1) Identify the relationship of safety, health, work environment and work discipline to work productivity, and (2) Identify the relationship of work environment on work discipline.Object of research is done in oil and gas industry large industrial class, namely LPG Plant Media Energy, PT. Media Karya Sentosa Gresik. The data used comes from questionnaires returned data and feasible to be processed a number of 108 respondents, who are employees of PT. Media Karya Sentosa Gresik. Summarized data with SPSS 11 software and using AMOS 16 to process the data statistically using Structural Equation Modeling (SEM). With SEM, obtained safety factor has a direct effect of negative but not significant effect on work productivity, occupational health factors have a significant positive direct effect on work productivity, work environment factors have a direct effect of positive but not significant effect on work productivity, and indirect influence on work productivity through work discipline, work discipline factors have a direct effect of negative but not significant effect on work productivity, and work environment factors have a direct effect of positive but not significant to the discipline of work.